2021
DOI: 10.3390/ijms22105169
|View full text |Cite
|
Sign up to set email alerts
|

The Prominin-1-Derived Peptide Improves Cardiac Function Following Ischemia

Abstract: Myocardial infarction (MI) remains the leading cause of death in the western world. Despite advancements in interventional revascularization technologies, many patients are not candidates for them due to comorbidities or lack of local resources. Non-invasive approaches to accelerate revascularization within ischemic tissues through angiogenesis by providing Vascular Endothelial Growth Factor (VEGF) in protein or gene form has been effective in animal models but not in humans likely due to its short half-life a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…27 The specific peptide-PR1P had been shown to promote angiogenesis by targeted binding VEGF and enhancing endogenous VEGF activity, which facilitated the repair of corneal, choroid, ear wound healing and hind limb ischemia. 19 Then PR1P peptides was revealed to 20 and in a mouse model of emphysema, it reduced acute lung injury by promoting the binding of VEGF to endothelial cells. 28 Studies on ONC model showed that PR1P peptide could enhance the effect of VEGF in promoting neuronal survival and ameliorating the neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 The specific peptide-PR1P had been shown to promote angiogenesis by targeted binding VEGF and enhancing endogenous VEGF activity, which facilitated the repair of corneal, choroid, ear wound healing and hind limb ischemia. 19 Then PR1P peptides was revealed to 20 and in a mouse model of emphysema, it reduced acute lung injury by promoting the binding of VEGF to endothelial cells. 28 Studies on ONC model showed that PR1P peptide could enhance the effect of VEGF in promoting neuronal survival and ameliorating the neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…19 And they were also showed to capture and upregulate endogenous VEGF in vivo, so that improved the angiogenesis and functional recovery in hind limb ischemia and myocardial ischemia. 19,20 In addition, a recent study in optic nerve compression (ONC) model, PR1P were demonstrated to enhance the survival of VEGF-driven neurons. 21 Whether these PR1P peptides could serve as anchor for VEGF sustained release?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PR1P could specifically interact with VEGF, stabilize VEGF, and increase the binding of VEGF to its receptors via potentiation of VEGF dimer formation 15 . In different animal models, PR1P was showed to enhance the repair of wound healing, hind limb ischemia and MI, reduced acute lung injury and protected neuron survival 16–18 . PR1P was also used to modify biomaterial scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…15 In different animal models, PR1P was showed to enhance the repair of wound healing, hind limb ischemia and MI, reduced acute lung injury and protected neuron survival. [16][17][18] PR1P was also used to modify biomaterial scaffold. By chemical covalent coupling, RP1P could immobilize VEGF on nano glasses effectively and increase the bioactivity of material scaffolds.…”
mentioning
confidence: 99%